Theatrical reviews by Stepan Vasilchenko: genre and style features (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article deals with Stepan Vasylchenko’s theatrical reviews, which have been first published on the pages of the edition “Rada”. In the research considerable attention is focused on the language, compositions of reviews, which represent the individual style of the author, and also on grounding of artistic value of plays, performances by Stepan Vasylchenko. The author of the article outlines the specificity of the review process and reviewer’s tasks.
Keywords: reviewing; theatrical review; actor; role; play; performance; epithet; personification; metaphor